2017
DOI: 10.1093/pcp/pcx126
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea WRKY70 Regulates the Expression of a Homeodomain-Leucine Zipper (HD-Zip) I Transcription Factor CaHDZ12, which Confers Abiotic Stress Tolerance in Transgenic Tobacco and Chickpea

Abstract: Drought and salinity are the two major environmental constraints that severely affect global agricultural productivity. Plant-specific HD-Zip transcription factors are involved in plant growth, development and stress responses. In the present study, we explored the functional characteristics and regulation of a novel HD-Zip (I) gene from chickpea, CaHDZ12, in response to water-deficit and salt-stress conditions. Transgenic tobacco lines over-expressing CaHDZ12 exhibited improved tolerance to osmotic stresses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 52 publications
3
44
0
Order By: Relevance
“…Sen et al . 35 reported that the enhanced drought resistance of transgenic tobacco plants is attributed to their increased sensitivity to ABA. Similarly, we observed an increase in the expression of the ABA biosynthetic gene, NCED1 , in both tobacco varieties, under PEG-induced water stress, suggesting that ABA-mediated stomatal closure is associated with an increase in drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Sen et al . 35 reported that the enhanced drought resistance of transgenic tobacco plants is attributed to their increased sensitivity to ABA. Similarly, we observed an increase in the expression of the ABA biosynthetic gene, NCED1 , in both tobacco varieties, under PEG-induced water stress, suggesting that ABA-mediated stomatal closure is associated with an increase in drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the HD-Zip I subfamily participates in abiotic stress response [6,19,26,27,28,29,30,31,32,33,45,50,56,59,60,61]. Cabello et al found that HaHB1 or AtHB13 can be up-regulated by drought and salt and can significantly improve salt tolerance and drought resistance by their ectopic expression to maintain cell membrane integrity [59].…”
Section: Discussionmentioning
confidence: 99%
“…Soybean HD-Zip I gene Gshdz4 was significantly up-regulated by alkali stress, and further results showed that it enhanced bicarbonate tolerance and response to osmotic pressure [32]. It was also reported that over-expressing one chickpea HD-Zip I gene, CaHDZ12 , resulted in improved tolerance to abiotic stress, and CaHDZ12 expression was regulated by CaWRKY70 [33]. The expression of Nicotiana attenuata HD-Zip I member NaHD20 was also shown to be positively correlated with ABA accumulation in leaves during water deficit and the expression of some dehydration-responsive genes [34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, transcriptome analysis could provide us great opportunity for revealing the genetic basis of higher adaptation of crop wild relatives (CWRs) and landraces to the counterpart of the cultivated species under various abiotic stresses (Srivastava et al, 2016). However, limited availability of abiotic stress tolerant cloned gene(s) has hampered the progress of functional genomics in chickpea (Deokar et al, 2015;Sen et al, 2017). Thus, in future mapbased cloning of abiotic stress tolerant gene(s)/QTLs could further illuminate our understanding of various mechanisms and key molecular players involved in drought, heat and cold tolerance in chickpea.…”
Section: Functional Genomic Resources For Drought and Heat Stress Tolmentioning
confidence: 99%